2016
DOI: 10.1016/j.ijpe.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Implementing sustainability in multi-tier supply chains: Strategies and contingencies in managing sub-suppliers

Abstract: Buying firms must pay increased attention to supply chain sustainability issues as they might be held responsible by stakeholders for non-sustainable supply chain activities. Frequently, sustainability problems occur upstream at the sub-supplier level. Building on the literature on multi-tier supply chains (MSCs), we investigated the strategies of buying firms in the food, apparel, packaging, and consumer electronics industries to manage the sustainability of second-tier suppliers and beyond. In particular, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
248
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(261 citation statements)
references
References 72 publications
(88 reference statements)
9
248
0
4
Order By: Relevance
“…The concept of sustainability is gaining increased global attention in the supply chain of fashion and textiles like the other sectors. Many times it might happen that firms' stakeholders hold the firm as a responsible party for any non-sustainable supply chain activity [21]. Stricter international and local regulations, customer awareness and increased competition are the main driving force behind sustainability [22], [23].…”
Section: Resultsmentioning
confidence: 99%
“…The concept of sustainability is gaining increased global attention in the supply chain of fashion and textiles like the other sectors. Many times it might happen that firms' stakeholders hold the firm as a responsible party for any non-sustainable supply chain activity [21]. Stricter international and local regulations, customer awareness and increased competition are the main driving force behind sustainability [22], [23].…”
Section: Resultsmentioning
confidence: 99%
“…Tachizawa and Wong (2014) proposed four strategies to manage sustainability in multi-tier supply chains-direct, indirect, work with third parties, and don't bother. Meinlschmidt et al (2018) provided evidence for three of these strategies and suggested that buyers use each one depending on the strengths of contextual factors (e.g., stakeholder salience), whereas Wilhelm et al (2016b) identified three factors-supply chain complexity, tier-one suppliers' sustainability capability, and sustainability dimension-that determine when and how buyers use such strategies on their sub-tier suppliers. Grimm et al (2014) identified 14 critical factors that influence the success of sub-suppliers' compliance with sustainability standards, whereas Hofmann et al (2018) revealed key enablers and barriers to implementing supply chain due diligence.…”
Section: Sustainable Supply Chainsmentioning
confidence: 99%
“…Horizontal complexity in particular is a main contingency for the LTSM strategy of focal buying firms (Wilhelm et al, 2016b). Therefore, the following is proposed: P2: The higher a buying firm's structural supply network complexity is, the higher its PSR.…”
Section: Environmental Uncertaintymentioning
confidence: 99%
“…We would further like to express our gratitude for the priceless engagement of our colleague and dear friend Betty Bea Cage. lower tier supplier environment (exemptions are e.g., Grimm et al, 2016 andWilhelm et al, 2016b). Thus, this study seeks to develop testable propositions in answering the following research questions: (1) How do buying firms manage their lower tier suppliers for sustainability?…”
mentioning
confidence: 99%